Synthesis and characterization of conducting Polyaniline@cobalt-Paraffin wax nanocomposite as nano-phase change material: Enhanced thermophysical properties. (August 2021) - B, Kalidasan; Pandey, A.K.; Shahabuddin, Syed; George, Mathew; Sharma, Kamal; Samykano, M.; Tyagi, V.V.; Saidur, R.
Abstract: Dispersion of conducting polymer-based nanocomposite in Phase Change Materials (PCMs) tends to enhance the thermophysical properties. Present work aims to synthesize and disperse conducting polyaniline@cobalt nanocomposite within the Paraffin matrix to improve the thermo-physical property. Polyaniline based nanocomposites with 1.0 and 2.0 wt% cobalt (PC1 and PC2) were sonicated with paraffin at different weight ratio of 0.1%, 0.5%, 1%, and 5% and characterization of nanocomposite dispersed phase change material was performed. Thermo-physical properties were analysed by using thermogravimetric analysis (TGA) and differential scanning calorimeter (DSC). Thermal conductivity of nanocomposite enhanced paraffin increased with increase in weight% of both PC1 and PC2 till 1% of its weight in paraffin and decreased for 5% of PC1 and PC2 concentration with paraffin. TGA readings observed drop in initial decomposition temperature of PPC1-5% (Paraffin with PC1 in 5% concentration) and PPC2-5% (Paraffin with PC2 in 5% concentration) by an amount of 08% and 12.4% respectively compared with base PCM Paraffin wax. DSC results of PPC1-0.1% and PPC2-0.5% showed 182.04 J/g and 170.86 J/g latent heat of fusion as compared to Paraffin wax. The samples were tested for 200 thermal cycles and the chemical stability and thermal property were compared with the fresh samples. Graphical abstract: Image 1